Design and Development of Hand Gesture Controlled Robot - Alapati Purnachandra Rao, Padmanabha Raju Chinda, Ragaleela Dalapati Rao, S. Pragna Sri, V. Varshitha (International Journal of Control and Automation, 2020)
Nowadays' electronic gadgets are assuming control over the world, and have become a gigantic piece of our life. The new notable developments permit truly provoked individuals to have the option to carry on with a superior life. These electronic gadgets can be controlled in different manners, yet the most famous strategy for control these days is signal control. This paper portrays the plan and execution of a robot that moves by hand motions. Accordingly, it expels the issue of utilizing joysticks or switches. The robot's speed is additionally controlled during its development by the hand. An accelerometer has been utilized that changes over various hand motions into information signals. The robot has two segments: the transmitting end and the receiving end. The transmitting end transmits the motion signals and the receiving end gets them. The accelerometer fills in as the sensor as it detects the various motions made by the hand and changes over them into simple signs which are additionally prepared and transmitted to the receiving end.